PENGARUH PENGETAHUAN MENDETEKSI KEKELIRUAN, PENGALAMAN AUDIT, PROFESIONAL, DAN KODE ETIK AUDITOR TERHADAP PENETAPAN TINGKAT MATERIALITAS - Mauritz Labora Lumban Gaol, - (2019)
This research was conducted to examine the effect of Knowledge of Detecting Error, Experience of Audit, Professional, and Auditor's Code of Ethics on Determination of Materiality Level at Public Accounting Firm in South Jakarta. The sample in this study amounted to 82 auditors who are in the Public Accounting Firm in South Jakarta selected by using Incidental Sampling which the sample are collected on 5 November until 5 December 2018. Obtained a total of 82 auditors. The final data produced are 82 samples ready for analysis and test. The analysis technique used is multiple linear regression and using an application of statistic names Partial Least Square (PLS) with significance level of 5%. The results of this study indicate that (1) Knowledge of Detecting Error has a significant effect on Determination of Materiality Level, (2) Experience of Audit has a significant effect on Determination of Materiality Level, (3) Professional has not a significant effect on Determination of Materiality Level, and (4) Auditor's Code of Ethics has not a significant effect on Determination of Materiality Level.